A aprendizagem funcional de construções imperativas em Português Língua Estrangeira - Rossi, Maria Antonietta (Educazione Linguistica Language Education, 2022)
Considering the didactic sequence model developed in the context of the glottodidatics to promote the real use of the target language in a socio-discursive perspective, the present work presents two proposals based on the pedagogical transposition process of authentic injunctive materials (‘cooking recipe’ and ‘assembly instructions’), with communicative and collaborative approaches, in order to promote for levels A2 and B1 the Meaningful Learning of imperative constructions in Portuguese as a Foreign Language, whose assimilation difficulty in the cognitive domain is recurrent in Italian-speaking students.